TATA CARA PENYIDIKAN TERHADAP PELAKU TINDAK PIDANA KEKERASAN TERHADAP ANAK DALAM KELUARGA - Sidauruk, Franky Hotman S.; Gultom, Maidin; Simatupang, Bachtiar (JURNAL PROINTEGRITA, 2020)
This study aims at determining and understanding the factors causing domestic violence, procedures for investigating perpetrators of domestic violence at the Medan City Police, and the obstacles faced in investigating domestic violence at the Kota Besar Police Station. In this research, library research was conducted. The results of the study show that the factors causing the crime of domestic violence are in addition to environmental factors, association, the influence of mass media, films, soap operas apparently also influenced the attitudes and actions of a child or family member. Culture encourages women (wives) to submit to their husbands, especially economically. Society does not consider domestic violence as a social problem, but rather as an internal problem between husband and wife, other people may not interfere. It is mistaken understanding of religious teachings assuming that men may rule over women. The process of investigating perpetrators of domestic violence is as follows: complaints from victims are received through the Women's and Children's Service Unit (PPA) Picket Officers. Furthermore the officer advised the victim to do a Visum et Repertum. The officer who receives the complaint will make a Minute of the Investigation of the victim. Based on information from the victim, the investigator will examine witnesses and call or arrest the suspect (depending on the results of Visum et Repertum) to conduct an examination of the suspect. In carrying out investigations of domestic violence, investigators experience several obstacles, namely: Domestic violence has a relatively closed (private) scope and is closely guarded because of the occurrence in the family environment; Domestic violence is often considered reasonable because it is believed that treating a wife as he wishes is the husband's right as the leader and head of the household; Domestic violence occurs in legal institutions, namely marriages. This fact causes the public to not respond to the complaints of the victims of the crime of domestic violence they experience.